Estudo da oxidação superficial do copolímero propileno/etileno durante o tratamento corona e sua influência no comportamento de termosoldagem - Mazzola, Nícolas Cardoso (2010)
Different ethylene-propylene copolymers (Ziegler-Natta and Metallocene) were exposed to corona discharge and analyzed by spectroscopic, morphological and fractionation techniques. Effects of different treatment configurations (types of electrodes and polarity of treatment) were explored, as well as the relationships between molecular configurations and corona discharge effects. Using FTIR, CRYSTAF, DSC and SEC techniques, the differences among the samples on ethylene content, stereo-defects and crystalline phases were identified. Measures of AFM, contact angle, XPS and FTIR-ATR were used to analyze the surface modification - energy, composition and topography - caused by the corona treatment. The results show that surface energy levels increase with the introduction of polar groups (hydroxyl, carbonyl and insaturations) forming a second phase with different elastic response during AFM measurement. The heat sealing behavior for the copolymers was measured by testing heat seal and hot tack. Theses results demonstrated dependence on the melting behavior of materials and molecular weight distribution of each sample. The films after corona treatment were sealed and the main difference observed was a changing on the failure mechanism, going from cohesive to delamination. The heat seal and hot tack maximum resistance dropped for all treated but the hot tack values for low temperatures increased, indicating the existence of polar interactions on the surface. Finally, the technique of fractionation by DSC / SSA demonstrated to be an important tool to correlate heat seal properties and melting behavior of propylene based materials. Cumulated heating enthalpy presented a good fit with values from conventional heat seal tests regarding heat seal initiation temperature.